(3OhQ GdMjdI aj JWhjQ GdbGfhf (B/ s - (3YHO Gddg HTjQ eSYhO NdjaI s; (3eMehO GdSbGs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2008)
(3dbO cGf ddMjdI GdOhQ GdYXje aj JWhjQ GdTQGFY eMd GdHMK (B((3GdbGfhf GdQheGfj (B- (3GdbGfhf GdEfLdjRj (B- (3GdTQjYI GdESdGejI (B- (3GdTQjYI GdjghOjI(B) (3hdbO GNJda gPG GdOhQ ef TQjYI Gdj GNQj aEPG cGf OhQ GdMjdI GYXe GKQG aj GdbGfhf GdQheGfj adbO LGA gPG GdOhQ aj GdeQJHI HGdfSHI ddbGfhf GdEfLdjRj GdG Gf OhQgG HGdfSHI dJWhjQ GMcGe GdTQjYI GdESdGejIcGf eMOhOG ddZGjI HSHH YehejI bhGYOgG Gdj LGfH Gf gPG GdOhQ LGA aj eQMdI eJCNQI LOG HYO GfbWGY GdhMj hGJSGY QbYI GdOhdI GdESdGejI(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe adSaI GdbGfhf hJGQjNg (B2008.s
(3HHdjhLQGajG(B: (3UaMGJ (B393-403.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3adSaI GdbGfhfs; (3GdbGfhf GdQheGfjs; (3TQjYI GdjghOs; (3GdMjdI s; (3CMcGe GdMjdIs; (3GdZTs; (3GdbQjfIs; (3GdUhQjIs; (3GdYbjOIs; (3GdJTQjYs; (3JGQjN GdbGfhf GdEfLdjRjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3adSaI GdbGfhfs